CURRENT ISSUES IN LINGUISTICS AND TRANSLATION STUDIES.: CURRENT ISSUES IN LINGUISTICS AND TRANSLATION STUDIES. - Бердекенова, Куляш (Журнал иностранных языков и лингвистики, 2025)
Linguistics is the study of language and how people use it. Translation studies focus on how to change words from one language into another. Both fields are important in our global world today. As technology and society change, new challengers and questions have come up in these areas. This report will explain some of the main issues that experts are dealing with now.